Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Section 7.5 - Multiplying with More Than One Term and Rationalizing Denominators - Exercise Set - Page 550: 76



Work Step by Step

We lose the square roots in the denominator by applying the difference of squares formula: $(a\sqrt{x}+b\sqrt{y})(a\sqrt{x}-b\sqrt{y})=(a\sqrt{x})^{2}-(b\sqrt{y})^{2}=a^{2}x-b^{2}y$ $\displaystyle \frac{15}{\sqrt{6}+1} \displaystyle \color{red}{ \cdot\frac{\sqrt{6}-1}{\sqrt{6}-1} }\qquad$ (rationalize) $ =\displaystyle \frac{15(\sqrt{6}-1)}{(\sqrt{6})^{2}-1} =\frac{15(\sqrt{6}-1)}{6-1} =\frac{15(\sqrt{6}-1)}{5}$ $=3(\sqrt{6}-1)$ $= 3\sqrt{6}-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.